Treason in Tudor England : Politics and Paranoia. - Smith, Lacey Baldwin (Princeton legacy library., 2014)
Lacey Baldwin Smith re-evaluates the Tudor mania for conspiracy in the light of psychological and social impulses peculiar to the age. Originally published in 1986. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly h.